Toward Smart Governance: A Bibliometric Analysis of Digital Transformation in Public Administration - Zubaidah , Siti; Hermansyah, Hermansyah; Yansyah, Putra; Firdaus, Firdaus; Desiwantara, Desiwantara (Journal of Social and Policy Issues, 2025)
This study aims to explore the global research trends in digital transformation within the field of public administration through a bibliometric analysis. Utilizing Scopus-indexed literature, the study applies a systematic review of articles published in English and classified under the social sciences subject area. The data collection was conducted on July 2, 2024, at 14:25 WIB, using the keywords “digital transformation” and “public administration,” (TITLE -ABS-KEY ("digital transfomation") OR TITLE-ABS-KEY ("public administration")) AND (LIMIT-TO (SUBJAREA, "SOCI")) AND (LIMIT-TO (DOCTYPE, "ar" ) ) AND ( LIMIT-TO ( LANGUAGE , "English" ) ), resulting in 12,871 relevant documents. The novelty of this study lies in its comprehensive mapping of academic discourse, highlighting key themes, emerging topics, and leading contributors in the intersection of digital technology and public sector governance. The findings reveal an increasing scholarly focus on Society 5.0, smart governance, and digital innovation as tools to enhance bureaucratic efficiency and citizen engagement. Importantly, the study provides valuable insights for practitioners and policymakers, particularly in developing countries like Indonesia, by identifying best practices and strategic directions to support effective digital governance and public service reform.